Managing the patient undergoing transcatheter aortic valve replacement with ongoing mitral regurgitation. (3rd August 2021) - Tirado-Conte, Gabriela; McInerney, Angela; Jimenez-Quevedo, Pilar; Carnero, Manuel; Marroquin Donday, Luis A.; De Agustin, Alberto; Witberg, Guy; Pozo, Eduardo; Islas, Fabian; Marcos-Alberca, Pedro; Cobiella, Javier; Koronowski, Ran; et al.
ABSTRACT: Introduction: Significant mitral regurgitation (MR) frequently coexists in patients with severe symptomatic aortic stenosis undergoing transcatheter aortic valve replacement (TAVR). These patients have worse clinical outcomes than those with non-significant MR, especially if MR persists after treatment of the aortic stenosis. The optimal treatment approach for this challenging high-risk population is not well defined. Areas Covered: This review aims to present the current literature on concomitant significant MR in the TAVR population, and to provide a comprehensive algorithmic approach for clinical decision-making in this challenging cohort of patients. Expert opinion: Concomitant mitral and aortic valve disease is a complex clinical entity. An exhaustive and comprehensive assessment of patient's clinical characteristics and mitral valve anatomy and function is required in order to assess the surgical risk, predict the MR response after AVR and evaluate the feasibility of percutaneous MV treatment if necessary. Further developments in transcatheter techniques will expand the indications for double valve treatment in operable and inoperable patients with concomitant significant MR and aortic stenosis.